Предмет: Алгебра,
автор: officialvarenikov90
А) (x+1)^2-(x-2)(x+4)
б) (a+b) (a-b) (a^2+b^2)
С решением
Ответы
Автор ответа:
1
Ответ: a) 9 б) a^4 - b^4
Объяснение:
а) (х+1)^2 - (x-2)(x+4) = x^2 + 2x + 1 - x^2 - 4x +2x + 8 = 9
б) (a+b)(a-b)(a^2+b^2) = (a^2 - ab + ab - b^2)(a^2+b^2) = (a^2 - b^2)(a^2 + b^2) = a^4 + a^2b^2 - a^2b^2 - b^4 = a^4 - b^4
Похожие вопросы
Предмет: Литература,
автор: degtyaranastasia13
Предмет: Биология,
автор: gelengermmash
Предмет: География,
автор: kirasmith0918
Предмет: Математика,
автор: alina510
Предмет: Литература,
автор: QweBnmAsd